Social robotics in music education: A systematic review - Martinez-Roig, Rosabel; Cazorla, Miguel; Esteve Faubel, José María (Frontiers in Education, 2023)
Social robotics applied to the educational context deals with proposals which start from the present to shape the future of what training in a specific subject can be. On this occasion, the aim sought is to investigate the connection between the utilisation of social robots and the teaching-learning processes that take place within a music learning environment. In order to carry out this research, the PRISMA model served as a reference to perform a systematic review of articles published in two of the most important scientific databases, Web of Science (WoS) and Scopus, since 2015. A total of 4 articles fulfilled the inclusion criteria. Our findings attest that social robotics still remains a practically unknown topic in relation to which hardly any experiences have been developed in classrooms. It is deemed necessary for Education in general, and more specifically for music teaching, not to be left aside from the advances that social robotics has already been channelling in other areas of our society with the aim of defining this twenty-first century.